Clima organizacional y su relación con el desempeño laboral del área comercial de la distribuidora Jorge Baron SAC. Iquitos 2023 - Angulo Puga, Renzo Renato (2024)
The objective of this study is to investigate the relationship between the organizational climate and the work performance of the commercial area of the Jorge Baron SAC distributor, Iquitos 2023. This study is framed in the descriptive correlational type, with a non-experimental research design and a focus cross section. The results indicate that a significant correlation is found between the organizational climate and the work performance of the distributor's commercial area, with a Pearson correlation value of 0.764. Furthermore, the bilateral significance value is less than 0.05 according to the decision rule.